O parcelamento do imóvel rural para fins urbanos sob a forma de sítios de recreio e o direito à cidade sustentável - Albuquerque, Patricia Cavalcanti (2018)
The present work, through the method of bibliographical research, seeks to analyze the parceling of rural property for urban purposes in the form of recreational sites and the implementation of the right to sustainable city in a context of activities for urban purposes that have been implemented in the rural area of the municipalities without the knowledge and control of the Municipal Public Power, responsible for the implementation of urban policy and which has the attribution, from the Federal Constitution, of promoting the appropriate territorial planning, through planning and control of the use, subdivision and urban land occupation, aiming to attend to the socio-environmental functions of property and the city, making possible the exercise of the right to sustainable city, according to directives of the Statute of the City. For that, it is necessary to analyze the concept and characteristics of rural and urban real estate, addressing the norms that should be applied, what is meant by the right to the sustainable city and the parceling of the rural property, especially regarding "recreational sites" , as well as which legal instruments can be used, in order to allow the integration of rural and urban environments, in favor of the exercise of the right to a sustainable city, avoiding undue expansion and the occurrence of damages to the environment.